The economics of soybean disease control - Kalaitzandonakes, Nicholas G., 1960- (CABI, 2019)
Although soybean is a major global crop, it suffers significant losses often because of an incomplete understanding of the extent of soybean diseases, and the feasibility and benefits of disease control. This book covers evidence on disease incidence and severity, management strategies and new technologies.